Influence of ultra-precision flycutting spindle error on surface frequency domain error formation. Issue 9 (February 2017) - Chen, Guoda; Sun, Yazhou; Zhang, Feihu; An, Chenhui; Chen, Wanqun; Su, Hao
Abstract The frequency domain error of the machined surface in the ultra-precision machining attracts more attention for its strong relationship with the functional requirements of the workpieces. As the key component of ultra-precision machine tool, the spindle error largely influences the machined surface errors. However, little attention has been paid to the influence of spindle error on the surface error formation mechanism in the frequency domain for ultra-precision flycutting. This paper deeply studies the influence of spindle error on the frequency domain error formation of machined surface in ultra-precision flycutting. The influence analysis of the spindle error is theoretically and experimentally carried out according to two different evaluation directions of the machined surface by flycutting, i.e., cutting direction and feed direction. The KDP crystal flycutting experiment is designed and conducted for the theoretical verification. The theoretical analysis has been found to agree well with the experimental results. This study is quite meaningful for deeply understanding the influence law of spindle error from the viewpoint of frequency domain. The research results are quite useful for the spindle error control, machined surface error prediction, machining process planning, and also show the potential use for the spindle (machine tool) design.